Pengaruh Variasi Bed Material Terhadap Kandungan Syngas Pada Dual Reactor Fluidized Bed Berbahan Bakar RDF - Maulana Zen, Farid Aziz; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika, 2022)
Abstract Dual Reactor Fluidized Bed is one type of gasification reactor which has two reactors, namely combustion reactor and gasification reactor. The working principle of this type of reactor is based on the fluidization process, where solid fuel will be treated like a fluid by utilizing bed material. In this study using a variety of types of sand that will be used as bed material, the types of sand used are silica sand, dolomite, and iron sand. The three types of sand used have the same size, namely 0.5?0.75 mm using 25 and 35 mesh. There are also several controlling variables such as the fuel used, namely RDF, the use of a temperature of 600°C in the gasification reactor and 650°C in the combustion reactor, using H2O agent gas with a constant temperature at 110°C at a pressure of 10 psi, and the air velocity of the blower of 9 m/s. The results of this study indicate that the use of different types of sand as bed material affects the resulting syngas content, which for this type of iron sand has the highest syngas content of 4.584% with details of 1.773% CO, 0.648% CH4, and 2.165% H2. Keywords : Fluidization, Bed Material, Dual Reactor Fluidized Bed